Диэлектрическая релаксация Гавриляки–Негами - Novikov, V. V.; Komkova, O. A.; Zharova, O. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A fractional differential operator was used to obtain the dependence of Havriliak–Negami complex susceptibility. The physical meaning of the fractional-order time derivative was analyzed. The solution of the differential equation with fractional derivatives makes it possible to predict anomalous dynamic dielectric properties in disordered materials (ferroelectrics, polymers, composites, etc.).